Problemy Dukhovnosti V Usloviyakh Sovremennoy Globalizatsii - Khurramovich, Togaev Shavkat (Research Parks Publishers, 2023)
The article attempts to study the problems of spiritual alienation of the individual in the context of globalization and this issue on a fairly scientific basis. Also in the article, when it comes to the spiritual alienation of a person, it is revealed that its essence, the reasons for its occurrence are analyzed from a socio-philosophical and moral point of view, and this is of great importance in understanding the essence of the issue. The article emphasizes that the problems of spiritual alienation of the individual in the context of globalization are not considered as a problem limited only to philosophy or ethics, but are also studied within the framework of other sciences, which are currently receiving much attention from many social sciences and the humanities.